Sosialisasi Mitigasi Bencana Gempa Bumi di Lingkungan Sekolah - Jusuf Leiwakabessy; Wanda Fiona Tarehy (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Indonesia that geologically situated at the convergence of three major tectonic plates, renders it susceptible to earthquakes. This research aims to provide earthquake disaster mitigation education to elementary school students through socialization activities. Despite the absence of accurate earthquake predictions, knowledge and preparedness can be conveyed early and consistently. Involving 40 students from fourth and fifth grades at SD Negeri Tanara, a combined method of lectures and game demonstrations was utilized. The research method, incorporating socialization in elementary schools with a combination of lectures and demonstrations, is considered effective in enhancing students' understanding of earthquake mitigation. Concrete steps can be taken by schools, and the practical knowledge imparted to students is crucial for their preparedness. The research results show that students responded enthusiastically to the material; most could articulate earthquake mitigation measures effectively. However, the evaluation also indicated that some students still encountered difficulties in communicating the material. These findings serve as valuable information for schools to develop students' understanding and skills in earthquake disaster mitigation efforts.